2016
DOI: 10.1177/1476750316661397
|View full text |Cite
|
Sign up to set email alerts
|

Involving incarcerated individuals in the research process: Perspectives of key stakeholders

Abstract: Given the considerable potential for participatory action research in correctional settings, this study gathered stakeholders' perspectives on involving adults in custody throughout the research process. Using mixed methods, the study identified participants' level of interest in involving prisoners in the research process to inform educational efforts to increase correctional participatory action research. Qualitative data were gathered from 94 prison administrators, Institutional Review Board throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…As an approach foregrounded in democratising the research process, valuing lived expertise and challenging power dynamics and social injustices (see Kim, 2016), we concur with Johnson et al (2018) assertion that participatory research can empower communities that are dis-empowered, and therefore has significant potential for social change in a youth justice setting. In their reflective paper on the evolution and use of participatory action research, Kidd et al (2018) advocate for its greater use with marginalised youth populations.…”
Section: Participatory Practices In Youth Justice Systemssupporting
confidence: 64%
“…As an approach foregrounded in democratising the research process, valuing lived expertise and challenging power dynamics and social injustices (see Kim, 2016), we concur with Johnson et al (2018) assertion that participatory research can empower communities that are dis-empowered, and therefore has significant potential for social change in a youth justice setting. In their reflective paper on the evolution and use of participatory action research, Kidd et al (2018) advocate for its greater use with marginalised youth populations.…”
Section: Participatory Practices In Youth Justice Systemssupporting
confidence: 64%
“…-Whilst prison staff buy-in is very important in a prison context and may indeed need some local, regional or national government prison policy support, as no research can successfully occur in prisons without addressing these 'gate-keepers' (Matfin, 2000), researcher buy-in is equally important. There is a lack of understanding amongst some researchers of the potentially positive impact of public involvement especially for research quality improvement; hence, education and training at all career stages may be useful (Biggane et al, 2019;Johnson et al, 2018). -Research in prisons can take a long time to set-up and conduct (Hayes & Senior, 2007), and involving public in research can take even more time and resources, particularly where PLiPs or PFLiPs need additional training (Domecq et al, 2014).…”
Section: Recommendationsmentioning
confidence: 99%
“…However, PPI in prisons has been described as under-developed (Awenat et al, 2017). A study of prison and research staffs' attitudes towards PLiP involvement demonstrated a lack of understanding and suggested that PLiPs were not seen as potential partners in the process (Johnson et al, 2018). One review outlined the possible ways that PLiPs could be involved, referring to the involvement of forensic mental health service users in research, but no examples of practice in prison were presented (Samele et al, 2008).…”
Section: Introductionmentioning
confidence: 99%